Announcements - Paetau, Michael (Journal of Sociocybernetics, 2013)
1). The 12th International Conference of Sociocybernetics will be held from 24-28th June 2013, in Merida, Mexico, and addresses »The sociocybernetics of social systems and social networks« in fields of complex social phenomena such as education, economy, interdisciplinary research, international relations, management, migration, new social media communication, scientific production, sustainability, social movements and systemic violence. The conference will discuss papers • reporting the empirical findings of research studies that apply sociocybernetics (both concepts and/or methodologies). • addressing the methodological and ethical issues associated with the creation and maintenance of research networks and with the reflective, self-referential aspects of research in sociocybernetics. • discussing theoretical and conceptual issues concerning how to effectively characterize social systems, social networks and the interactions of social actors. 2). The next World Congress of Sociology will be hosted by the Japan Sociological Society (JSS) from 13-19 July 2014. RC 51 will be present with 18 sessions.